Pengaruh Risiko Investasi Dan Profitabilitas Terhadap Return Saham Perusahaan Otomotif Yang Terdaftar di Bursa Efek Indonesia - Linggarsari, Ovi; Winarko, Sigit Puji; Tohari, Amin (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Stock Return is the rate of return in the form of profits or losses received by investors during certain periods. The aim of this research is to determine the influence of market risk, business risk, financial risk, profitability (ROA) on stock returns both partially and simultaneously in automotive companies. listed on the Indonesian Stock Exchange. This research uses a purposive sampling method as a way to select samples, resulting in 15 companies that meet several research criteria, namely: Automotive companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Automotive companies that always report complete financial reports for the 2021-2023 period. Automotive companies that have profits during the 2021-2023 period. The data analysis methods used are normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination test (R2), F test, and T test. The data used in this research is secondary data originating from reports. company annual financials. The data analysis technique used is descriptive statistical analysis and multiple linear analysis using the SPSS version 29.0 program. The results of this research are that market risk, financial risk, and profitability (ROA) have a negative effect on stock returns. Meanwhile, business risk has a positive effect on stock returns.